N-Acetylcysteine inhalation improves pulmonary function in patients received liver transplantation - Li, Xiaoyun (Biosci Rep, 2018)
Postoperative pulmonary complications (PPCs) following orthotopic liver transplantation (OLT) are associated with high morbidity and mortality rates. The effect of N-acetylcysteine (NAC) inhalation on the incidence of PPCs and the outcomes of patients undergoing OLT is unknown. This prospective randomized controlled clinical trial was conducted to investigate the effect of NAC inhalation during OLT on PPCs. Sixty patients were randomly assigned to the NAC group (n = 30) or the control group (n = 30) to receive inhaled NAC or sterilized water, respectively, for 30 min before surgery and 3 h after reperfusion. The incidence of early PPCs and outcomes including survival rate were assessed. Biomarkers including tumor necrosis factor (TNF)-α, interleukin (IL)-8, Clara cell secretory protein (CC16), intercellular adhesion molecule (ICAM)-1, and superoxide dismutase (SOD) were measured in exhaled breath condensate (EBC) at T1 (before surgery) and T2 (at the end of operation) as well as in serum at T1, T2, T3 (12 h after operation), and T4 (24 h after operation). A total of 42 patients (20 in the NAC group and 22 in the control group) were enrolled in the final analysis. Atomization inhaled NAC significantly reduced the incidence of PPCs after OLT. The levels of TNF-α, IL-8, CC16, and ICAM-1 in EBC were significantly lower, and SOD activity was higher, at T2 in the NAC group; similar data were found in serum at T2, T3, and T4. In summary, perioperative NAC inhalation may reduce the incidence of PPCs and improve patient outcomes after OLT.